(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
AI has the ability to increase productivity and economic growth. It may improve decision-making and quality while also encouraging creation of new services, markets, & even industries. This article looks at how artificial intelligence affects internet buying behavior. The major goal of this study is to investigate influence of AIon purchase choices in digital marketing. Finally, influence of AI on purchase choices in digital marketing cannot be overstated. It has altered the way users engage with online platforms by providing tailored suggestions, real-time customer assistance, and effective supply chain management. As AI technology progresses, organizations must embrace and leverage its promise to provide greater consumer experiences. Understanding and responding to changing client demands and concerns allows businesses to remain competitive and grow in the quickly digital world of online commerce.